2021
DOI: 10.3390/robotics10010012
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Human-Robot Interactions for Multiple Unmanned Aerial Vehicles

Abstract: Advances in unmanned aircraft systems (UAS) have paved the way for progressively higher levels of intelligence and autonomy, supporting new modes of operation, such as the one-to-many (OTM) concept, where a single human operator is responsible for monitoring and coordinating the tasks of multiple unmanned aerial vehicles (UAVs). This paper presents the development and evaluation of cognitive human-machine interfaces and interactions (CHMI2) supporting adaptive automation in OTM applications. A CHMI2 system com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…We want to continue exploring applications and extend this work to human studies to investigate the framework's effectiveness for complex teleoperation tasks. A domain of interest where our ideas can apply are one-tomany (OTM) scenarios where a human operator needs to monitor and coordinate multiple multiple autonomous vehicles [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We want to continue exploring applications and extend this work to human studies to investigate the framework's effectiveness for complex teleoperation tasks. A domain of interest where our ideas can apply are one-tomany (OTM) scenarios where a human operator needs to monitor and coordinate multiple multiple autonomous vehicles [39].…”
Section: Discussionmentioning
confidence: 99%
“…Neglect is mainly due to the robots competing for operator attention [38]. In [39], the authors propose real-time measurements of neurophysiological parameters to estimate workload as a potential input to new forms of adaptive automation.…”
Section: Related Workmentioning
confidence: 99%
“…Hence, these studies failed to implement a conventional ANFIS paradigm to produce accurate results of the online inference of MWL. Whereas studies by Zhang et al and Wang et al [46,58,59] demonstrated large time intervals, Lim et al [52] lacked the ability to demonstrate an inference of MWL during an online validation. Moreover, recent studies have outlined the importance of investigating the features contributing to the performance of the respective model used [50,51].…”
Section: Multimodal Fusion For Inferring Mwlmentioning
confidence: 99%
“…In addition to this, some studies compare several classification models when performing MWL estimations [50,51]. The use of regression models, such as Neuro Fuzzy Systems (NFS) [46,52,53] and Gaussian process regression [44], provides a continuous estimation of MWL but is less reported. Many of the studies that perform multimodal data fusion implement ML techniques that perform the calibration and validation in offline processing.…”
Section: Multimodal Fusion For Inferring Mwlmentioning
confidence: 99%
See 1 more Smart Citation